Q↔D Kinetics: Nucleation, Propagation, and Kinetic Traps in a Tetra-Stranded Hereditary Polymer - Barack Ndenga (Publisher, 2025)
Thermodynamic stability alone is insufficient to establish the feasibility of a hereditary polymer. Even if a tetra-stranded genetic architecture is energetically favorable under defined conditions, its biological relevance depends critically on kinetic accessibility. In this work, I develop a kinetic framework for Q-DNA, a canonical tetra-stranded hereditary polymer, and analyze the Q↔D interconversion problem through the lens of nucleationtheory, free-energy barriers, and metastability. I show that Q-DNA may occupy regions of parameter space where it is thermodynamically stable yet kinetically inaccessible, and I define strategies—environmental and molecular—for overcoming these barriers. This framework yields accessibility–stability maps that render tetra-stranded heredity experimentally testable and falsifiable.
Thermodynamic stability alone is insufficient to establish the feasibility of a hereditary polymer. Even when a genetic architecture is energetically favored, it may remain biologically irrelevant if its formation and regeneration are blocked by kinetic barriers. This limitation is well established for nucleic acids, where multistranded structures often exhibit slow folding pathways, metastable intermediates, and deep kinetic traps. In this work, I develop a kinetic framework for Q-DNA, defined as a canonical tetra-stranded hereditary polymer, and analyze the Q↔D interconversion problem through the lenses of nucleation theory, propagation dynamics, and kinetic trapping. I show that Q-DNA may occupy regions of parameter space where it is thermodynamically stable yet kinetically inaccessible, and I explicitly separate stability from accessibility as independent feasibility criteria. I model Q-DNA formation as a nucleation-and-growth process, identify critical nucleus sizes and free-energy barriers, and characterize the emergence of metastable non-hereditary states arising from mis-registration, partial bundle locking, and topological frustration. These considerations lead to the introduction of accessibility–stability maps, which classify tetra-stranded genetic systems into regimes ranging from irrelevant to viable. Finally, I outline generic strategies for overcoming kinetic barriers—including temperature cycling, ionic tuning, molecular crowding, and chaperone-like assistance—and formulate falsifiable predictions regarding hysteresis, rate dependence, and long-lived intermediates. By treating kinetics as a decisive filter rather than a secondary detail, this work renders tetra-stranded heredity experimentally testable and positions Q-DNA as a rigorously constrained hypothesis at the intersection of biophysics, theoretical biology, and synthetic genetics.